THE LANDSCAPE AND RECREATION PROJECT OF THE HEAT CENTER WAY AND ITS ENVİRONS OF THE MAIN CAMPUS OF ZONGULDAK KARAELMAS UNİVERSİTY - Gülez, Sümer; Çorbacı, Ö. Lütfü; Topay, Mehmet (Bartın Üniversitesi, 2005)
Open and green spaces in the university campuses are generally planned as a park that is important for both faculty and students to be in a qualitative and secure atmosphere. This condition mostly affects on the qualities of education and teaching positively. The heat center way and its environs of the main campus of the ZKU was chosen a case area. The project, which was prepared depending on recreational aims and landscape planning principles, was developed and determined with the various scenarios. Besides, the project, which was handed out to the Rector Office with a model for implementation, included the scenarios of implementation processes. The Project has been composed of only a part of ZKU central campus. Nevertheless, this Project has been integrated to whole campus design. As a result, the campus planning totalitarian and improvable for the future uses.

Üniversite kampüslerinde açık ve yeşil alanların genelde bir park şeklinde planlanması, gerek öğretim elemanları gerekse öğrencilerin kaliteli ve güvenli bir şekilde yaşamaları açısından önemlidir. Bu durum eğitim ve öğretimin kalitesine genellikle olumlu olarak yansır. Yapılan çalışmada; ZKÜ Merkez Kampüsü ısı merkezi yolu ve yakın çevresi çalışma alanı olarak seçilerek, rekreasyonel açıdan ve peyzaj planlama ilkeleri gözetilerek hazırlanan ve farklı öneriler doğrultusunda geliştirilen proje tanıtılmakta ve irdelenmektedir. Ayrıca, uygulanması açısından Rektörlük Makamına maketi ile birlikte sunulan projenin uygulama aşamalarındaki önerilere de yer verilmiştir. Yapılan bu çalışma, ZKÜ merkez kampüsün sadece önemli bir bölümünü incelemektedir. Ancak, tasarlanan proje üniversite kampüsünün bütününe entegre olabilecektir. Sonuç olarak, kampüs planları bütüncül ve gelişmeye açık olmalıdır.
ZKÜ MERKEZ KAMPÜSÜ ISI MERKEZİ YOLU VE ÇEVRESİ PEYZAJ VE REKREASYON PROJESİ